Prognostic Impact of TTF-1 Expression in Non-Squamous Non-Small-Cell Lung Cancer: A Meta-Analysis - Kim, Jung Han (J Cancer, 2018)
Thyroid transcription factor-1 (TTF-1) is overexpressed in up to 95% of primary lung adenocarcinoma while negative for almost all squamous cell carcinomas. TTF-1 expression has been investigated as a prognostic factor in non-small-cell lung cancer (NSCLC) with conflicting results. We conducted this meta-analysis to gain a better insight into the prognostic role of TTF-1 in patients only with non-squamous (non-SQ) NSCLC. A systematic computerized search of the electronic databases including PubMed, PMC, EMBASE, Web of Science, and Cochrane Library was performed. From 21 studies, 6,451 patients were included in the combined analysis of hazard ratios (HRs) with 95% confidence intervals (CIs) for overall survival. Compared with patients with non-SQ NSCLC showing negative TTF-1 expression, those with tumors harboring TTF-1 overexpression had significantly better survival (HR = 0.49, 95% CI: 0.42-0.57, p < 0.00001). Subgroup analyses revealed that TTF-1 expression significantly correlated with a better prognosis in stage I (HR = 0.65, 95% CI: 0.50-0.84, p = 0.0008) as well as stage III-IV non-SQ NSCLC (HR = 0.38, 95% CI: 0.29-0.49, p < 0.00001). In conclusion, this meta-analysis demonstrates that TTF-1 overexpression is a favorable prognostic factor in patients with non-SQ NSCLC. The subgroup analyses indicate that TTF-1 is a good prognostic marker for survival not only in early-stage but also in advanced non-SQ NSCLC.